Cultural Capital of Recruitment Decision‐Makers and its Influence on their Perception of Person‐Organisation Fit of Skilled Migrants. (18th December 2018) - Almeida, Shamika; Waxin, Marie‐France; Paradies, Yin
ABSTRACT: This article examines how recruitment decision‐makers' cultural capital can influence their concerns about the organizational fit of skilled migrants (SM). We used survey data and interviews with Information Technology organizations in Australia. The study highlights the decision‐makers' relatively poor understanding of non‐western cultures and how it negatively influences their perception of candidates from non‐western backgrounds. Furthermore, this study also notes how organisational cultural values and decision‐makers' exposure to diverse cultures can influence their assumptions about the value of international qualifications and work experiences. Similarly, it can also influence how they assess the perception of fit based on a candidate's appearance and communication style. Consequently, the cognitive biases and judgements of resource acquisition managers can act as gatekeepers who keep non‐western SM out of the organizational resource pool. The article concludes by noting the importance of human resource practices that seek to develop cultural capital of decision‐makers.